2019
DOI: 10.1016/j.geb.2019.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Rhetoric matters: A social norms explanation for the anomaly of framing

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 92 publications
5
49
1
Order By: Relevance
“…Across four treatments, participants received one random truthful norm-nudge that emphasized 'moral suasion' based on either what other participants previously did (empirical message) or approved of doing (normative message). Motivated by existing literature that recognizes the relevance of framing effects (e.g., Andreoni, 1995;Levin et al, 1998;Kahneman, 2003;Alekseev et al, 2017, on the relationship between framing and norms, see Chang et al, 2019), we also varied the framing of the norm messages and presented them in either a positive way (majority did not cheat / did not approve of cheating) or an inverted and equivalent negative way (minority cheated / approved of cheating).…”
Section: Introductionmentioning
confidence: 99%
“…Across four treatments, participants received one random truthful norm-nudge that emphasized 'moral suasion' based on either what other participants previously did (empirical message) or approved of doing (normative message). Motivated by existing literature that recognizes the relevance of framing effects (e.g., Andreoni, 1995;Levin et al, 1998;Kahneman, 2003;Alekseev et al, 2017, on the relationship between framing and norms, see Chang et al, 2019), we also varied the framing of the norm messages and presented them in either a positive way (majority did not cheat / did not approve of cheating) or an inverted and equivalent negative way (minority cheated / approved of cheating).…”
Section: Introductionmentioning
confidence: 99%
“…Across four treatments, participants received one random truthful norm-nudge that emphasized 'moral suasion' based on either what other participants previously did (empirical message) or approved of doing (normative message). Motivated by existing literature that recognizes the relevance of framing effects (e.g., Andreoni, 1995;Levin et al, 1998;Kahneman, 2003;Alekseev et al, 2017, on the relationship between framing and norms, see Chang et al, 2019), we also varied the framing of the norm messages and presented them in either a positive way (majority did not cheat / did not approve of cheating) or an inverted and equivalent negative way (minority cheated / approved of cheating).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we want to explore if and to which degree the behavior we observe can be explained by social norms. Building on the social identity model by Kranton (2000, 2005), Chang et al (2019) present evidence that framing an experiment in a particular context evokes certain social norms which in turn affect people's choices. We posit that differently framed decision situations raise different social norms for (dis)honesty -that is, people might decide to lie or not to lie depending on the prevailing social norms in the specific situational context.…”
Section: Social Norms As a Possible Explanation For (Dis)honestymentioning
confidence: 81%
“…While Cohn et al (2014) prime subjects on their (financial) professional identity, a number of studies have shown that framing an experimental task in a financial way also discourages cooperation, and thus the more "moral" behavior, in a Prisoner's dilemma (Liberman et al, 2004;Ellingsen et al, 2012Ellingsen et al, , 2013. Turning to framing, which plays an important role in our experiment, the evidence of contextual instructions' effects on behavior is mixed in dictator games: Dreber et al (2013) report no (social or anti-social) framing effects, while Chang et al (2019) show that framing an experiment in a particular context can evoke certain social norms which in turn also affect people's choices. 3 We examine financial professionals' dishonest behavior in a truth-telling experiment where participants have to report a number where truth-telling is costly.…”
Section: Introductionmentioning
confidence: 78%